Implementasi Pembelajaran Berdiferensiasi Melalui Virtual Reality dalam Kurikulum Merdeka - Rassyi, Sultan Fakhrur; Isro’ullaili; Mauludin, Nurman (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
This study aims to examine the implementation of differentiated learning through Virtual Reality (VR) technology. Differentiated learning emphasizes the importance of accommodating individual students' learning needs based on their interests, levels of understanding, and learning styles. VR technology was chosen as an innovative tool to enrich the learning experience, allowing students to explore material immersively and interactively. This research employs a qualitative approach based on a literature review, analyzing relevant studies on differentiated learning, the use of VR technology in education, and its alignment with learning objectives. The findings indicate that VR has the potential to enhance student engagement and motivation in learning while supporting more flexible and personalized learning strategies. However, challenges such as technological infrastructure limitations and the need for teacher capacity building in effectively utilizing VR were identified. The conclusion of this study is that integrating VR into differentiated learning holds significant potential for achieving educational goals, provided there is adequate technological support and teacher capacity development.